Feelin : creative practice, pleasure, and Black feminist thought - Judd, Bettina (Northwestern University Press, 2022)
"Through interviews, close readings, and archival research, Bettina Judd draws on the fields of affect studies and Black studies to analyze the creative processes and contributions of Black women artists"--